Infektionen durch multiresistente Erreger: Erreger, Resistenzmechanismen und etablierte Therapieoptionen - Richter, Daniel; Brenner, Thorsten; Hochreiter, Marcel; Heininger, Alexandra; Weigand, Markus A.; Lichtenstern, Christoph (Der Anaesthesist, 2019)
The increase in resistant pathogens has long been a global problem. Complicated life-threatening infections due to multidrug-resistant pathogens (MRD) meanwhile occur regularly in intensive care medicine. An important and also potentially modifiable factor of the rapid spread of resistance is the irrational use of broad spectrum antibiotics in human medicine. In addition to many other resistance mechanisms, beta-lactamases play an important role in Gram-negative pathogens. They are not uncommonly the leading reason of difficult to treat infections and the failure of known routinely used broad spectrum antibiotics, such as cephalosporins, (acylamino)penicillins and carbapenems. Strategies for containment of MRDs primaríly target the rational use of antibiotics. In this respect interdisciplinary treatment teams, e.g. antibiotic stewardship (ABS) and infectious diseases stewardship (IDS) play a major role.